Measuring the economic gain of investing in girls : the girl effect dividend - Chaaban, Jad; Cunningham, Wendy (2012)
Although girls are approximately half the youth population in developing countries, they contribute less than their potential to the economy. The objective of this paper is to quantify the opportunity cost of girls' exclusion from productive employment with the hope that stark figures will lead policymakers to reconsider the current underinvestment in girls. The paper explores the linkages between investing in girls and potential increases in national income by examining three widely prevalent aspects of adolescent girls' lives: early school dropout, teenage pregnancy and joblessness. The countries included in the analysis are: Bangladesh, Brazil, Burundi, China, Ethiopia, India, Kenya, Malawi, Nigeria, Paraguay, Senegal, South Africa, Tanzania, and Uganda. The authors use secondary data to allow for some comparability across countries. They find that investing in girls so that they would complete the next level of education would lead to lifetime earnings of today's cohort of girls that is equivalent to up to 68 percent of annual gross domestic product. When adjusting for ability bias and labor demand elasticities, this figure falls to 54 percent, or 1.5 percent per year. Closing the inactivity rate between girls and boys would increase gross domestic product by up to 5.4 percent, but when accounting for students, male-female wage gaps and labor demand elasticities, the joblessness gap between girls and their male counterparts yields an increase in gross domestic product of up to 1.2 percent in a single year. The cost of adolescent pregnancy as a share of gross domestic could be as high as 30 percent or as low as 1 percent over a girl's lifetime, depending on the assumptions used to calculate the losses.